MANUFACTURE AND TESTING OF VIBRATION TEST SCHEMES FOR PIPING SYSTEMS - Ali, Ali; Saputra, Hendiawan Nugraha Aldi (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2024)
Piping system is the distribution of fluids through pipes. This is often in everyday life, an example is the water pipe in every house that is used to fulfill desires and in the industrial field pipes are often used to distribute petroleum fluids as well as offshore and onshore. Supports have a very important role to overcome the loads that occur at points that experience excessive loads caused by the weight of pipes and other devices. In general, dynamic failures in pipe systems are caused by resonance from the vibrations of the pipe stretch. Therefore, this research is intended to determine the effect of valve opening variation and pedestal distance variation on vibration in the pipe system so that it can be used for consideration in designing a piping system. This research uses an experimental approach starting with the preparation of a vibration test scheme and then testing using a vibration meter. The test data was processed and statistically analyzed so that it was found that at 100% valve opening, the largest value is at a pedestal distance of 180 cm with a flow rate of 2.8 m/s2 and the largest 50% valve opening is at the same pedestal distance of 180 cm with a flow rate of 2.3 m/s2. The farther the pedestal distance, the greater the vibration and deflection and the greater the flow discharge produced, the higher the vibration produced